Relationship between Knowledge, Attitude, and Behavior on Head and Neck Cancer among Health Workers and Community in Bandung, Indonesia - Yussy Afriani Dewi; Ifiq Budiyan Nazar (Faculty of Medicine, Universitas Padjadjaran, 2021)
Head and neck cancer is the sixth most common cancer in the world with increasing incidence and mortality in the last three decades. The hidden location of head and neck tumors and their atypical symptoms cause difficulties in diagnosis. Most patients are first diagnosed at an advanced stage. Several factors allegedly related to the incidence of head and neck cancer are knowledge and attitude of the public on early detection of cancer. This study aimed to determine the relationship between knowledge, attitude, and behavior of health workers and community towards head and neck cancer in Bandung, Indonesia. This was a cross-sectional analytical descriptive study using chi-square test as the statistical test. Subjects for this study were sampled using the proportional cluster random sampling on health care workers and community in 30 community health centers in Bandung City during the period of July–August 2019. Data were obtained through a questionnaire distributed to the subjects. This questionnaire included items on knowledge, attitude, and behavior towards head and neck cancer. Of the 650 respondents, most were 40-49 years old (25%), female (62,2%), patients (74%), high school (49%). The levels of knowledge and attitude have a significant relationship with the behavior of early detection of head and neck cancer (p=0.015). The awareness and knowledge of health workers and community on early detection of head and neck cancer are high in Bandung, Indonesia.